(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Hanging is a form of violent asphyxial death and it is the most common mode of suicide in India. This study was conducted in the dept. of Forensic Medicine and Toxicology AIIMS, Bhubaneswar. In this study, 45.4 % of victims belongs to the 21-30 years age group. In terms of sex distribution in out of 67 cases 39 were males and 28 were females. Also 62 victims were married. Soft and broad ligature materials like saree, chunni, bedsheets etc were noticed in 36 cases followed by rough and tough ligature materials like plastic rope in 31 cases. 78 % of cases were complete and atypical hanging. Congestion of laryngeal mucosa was present in 46 number of cases. Preventive measures like awareness programs should be there focusing on young married individuals specially males.